Extinction ratio improvement by an advanced NOLM setup - Striegler, A; Schmauß, Bernhard (IEEE Photonics Technology Letters, 2006)
We present a nonlinear optical loop mirror (NOLM)-based setup which is optimized for regeneration of signals with a poor extinction ratio caused by, e.g., high powered ghost pulses. In a conventional NOLM, the improvement of the extinction ratio is limited by the input extinction ratio or insufficient amplitude jitter reduction. These limitations can be overcome by an additional directional phase shifter. According to numerical simulation, the extinction ratio can be improved from 6 dB up to several 10 d
lhft_intern.bib::striegler06a